The Anti-Corruption Legal Revolution: Updates to the Latest Laws in 2025 - Hana, Bella Suspia; Mukhlis, Mukhlis (Yayasan Baru Haji Samsudin, 2025)
This study provides a comprehensive analysis of the anti-corruption law landscape in Indonesia during 2025, a year characterized by significant legislative dynamics and judicial reviews rather than the enactment of a new, comprehensive anti-corruption act. The primary legal framework remains Law No. 31/1999 juncto Law No. 20/2001. A pivotal development in 2025 was the controversial implementation of Law No. 1/2025 on State-Owned Enterprises (SOEs), which reclassified SOE directors and commissioners as non-state officials. This change, coupled with the formalistic implementation of the 2025 Presidential Regulation on Procurement (Perpres PBJ), potentially limits the jurisdiction of the Corruption Eradication Commission (KPK) and the State Audit Body (BPK), creating significant legal uncertainty. The research uses qualitative legislative analysis to argue that the